PREGNANT WOMEN EMPOWERMENT IN MONITORING FETAL WELLBEING THROUGH FETAL MOVEMENT COUNT MOBILE APPLICATION - Ika Yudianti; Dessy Amelia; Nur Eva Aristina; Nina Primasari (SEAJOM: The Southeast Asia Journal of Midwifery, 2022)
Fetal movement is one of the main indicators of fetal well-being in the womb. For this reason, every pregnant woman should be able to calculate and interpret the results of fetal movement calculations every day, so that early detection of fetal pathology can be identified by the family. Most pregnant women are not used to it and have not received information about how to calculate fetal movement. Another obstacle in calculating fetal movements is the forgetting factor. For this reason, a tool is needed to familiarize mothers with counting fetal movements every day. Existing tools still have some drawbacks. This study aims to develop an android-based application called "Kick Count", as a tool for pregnant women to count fetal movements every day. The research method uses R&D which consists of: exploring potential problems, gathering information, product design, design testing, design improvement, and product testing. The results of product trials by media experts, material experts, and groups of pregnant women state that this product is very suitable for use by pregnant women in the community. Things that still need to be perfected for the next stage are reducing memory and integrating installation instructions into the application.